Urine drug screening: A guide to monitoring Tx with controlled substances. - Hayes, John; Fox, Kristen (Journal of Family Practice, 2021)
Avoid error by ordering the appropriate test at a risk-based frequency. Be alert to sources of false-positives and adulteration. Be careful not to overreact to unexpected results.